What Drives Consumers' Purchase Intention in Live Commerce? An Extended Technology Acceptance Model - Marsha Alifia Vesthi; Faris Muslihul Amin; Ilham Ilham (ARBITRASE: Journal of Economics and Accounting, 2026)
The rapid development of digital technology has increased the popularity of TikTok Live Shopping as an emerging social commerce platform for online purchasing. However, limited studies have examined consumer purchase intention in this context using an extended Technology Acceptance Model (TAM). This study aims to analyze the effects of Perceived Usefulness, Perceived Ease of Use, Perceived Enjoyment, Perceived Value, and Trust on Purchase Intention, with Attitude serving as a mediating variable. The novelty of this study lies in integrating Perceived Value and Trust into the TAM framework to better explain consumer purchase intention in live social commerce. A quantitative approach was employed using a survey of 261 university students in Surabaya who had previously purchased products through TikTok Live Shopping. Respondents were selected using purposive sampling, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The model explained 61.0% of the variance in Attitude (R² = 0.610) and 46.5% of the variance in Purchase Intention (R² = 0.465). Perceived Value had the strongest positive effect on Trust (? = 0.570, p < 0.001), while Trust significantly influenced both Attitude and Purchase Intention. However, Perceived Enjoyment and Perceived Usefulness did not significantly influence Attitude. These findings highlight the importance of Trust and Perceived Value in shaping consumer purchase intention, provide empirical support for extending TAM in the context of TikTok Live Shopping, and offer practical insights for platform providers and online sellers.